Menyemai wawasan moderat pada siswa-siswi MAN 1 Kota Kediri melalui seminar moderasi beragama - Anwar, Muhammad Rosihan; Nasrilia, Yonanda Kumala; Awwalina P., Yasmine Azzahra; Khudin, Ahmad Mifta; Virgiawan, Muhammad Raka; Rozaq, Falih Shafiu; Nur Halizah, Khaililla Dara; Ummah, Rachmatul; Ainani’ma, Waffa (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
Community service through the Student Work Course (KKM) at UIN Maulana Malik Ibrahim Malang aims to improve human resources and community welfare. One of the KKM activities is a religious moderation seminar at MAN 1 Kota Kediri on May 4, 2024. This seminar, attended by 30 participants from various student organizations, aims to strengthen the understanding of religious moderation among students to address social and religious challenges. The seminar planning includes selecting speakers, themes, event structure, and target participants. Luthfi Dharmawan, an expert in religious moderation, was the main speaker. The seminar, themed "Talking Religion Without Drama: Navigating Moderation in Everyday Life," lasted two hours and discussed the importance of understanding, truth, and wisdom in religion. The results showed increased student awareness of religious moderation and helped the madrasa disseminate moderation values. Recommendations include expanding the seminar's reach in the future.